The effectiveness of multimedia language courseware on secondary school students motivation for learning English - Hashemyolia, Shayeshteh; Mohd Ayub, Ahmad Fauzi; Moharrer, Zahra (Mediterranean Center of Social and Educational Research, 2015)
Integration of multimedia language courseware (MLC) has been wildly practiced in teaching and learning of English as a Foreign Language (EFL). The purpose of this study was to determine the effects of MLC on secondary students’ motivation in its five dimensions of intrinsic, extrinsic, self-efficacy, relevance, and anxiety in a public school in Iran. This study utilized a quasi-experimental method using only the post-test design which consists of 62 participants in two groups. The control group was taught in only the traditional method and the experimental group was also taught in a face-to-face environment while using MLC. In addition, inferential statistical analyses revealed that there was a significant difference between the groups on the overall motivation in support of the experimental group. Accordingly, MLC can motivate learners to engage in the learning process and they are interested in and satisfied with utilizing MLC in the classroom.